NOTES ON THE POSSIBILITY AND THE JUSTIFICATIONS POPULATION RESETTLEMENT PROJECTS IN LIBYA - Attir, Dr. Mustafa (Dirasat in Economics and Business, 1972)
In this theoritical paper, an attempt has been made to answer two er questions : 1) Is it possible to resettle those Libyans who are living in small groups scattered in the Libyan desert ? 2) And, what are the justifications, if any, of population resettlement projects ? The writer sees that it is possible to develop a number of popula tion centers. Libyans living in scattered oasis are to be moved into such centers. However, it is suggested that socio-economic research should be carried on among the small communities for whom the population centers are going to be developed. Such research should focus on providing planners with an adequate picture of the major social and economic characteristics of these small communities. Because, it is very important that planners know in advance the age and sex distributions of individuals of these communities, their skills, mojor values, habits, customs, attitudes, and even their level of aspira tions. In other words, planners should be aware of the dominant sub cultures and social structures in order to be able to draw plans of practicle and suitable population resettlement projects.